Short Term Deflation of Stomach during Laparoscopic Surgery: Nasal versus Oral Route - Quasi-Experimental Study - Iftikhar, Izza; Abdullah, Hassam; Sohail, Amir; Ilyas, Hafiza Ayesha; Saeed, Muhammad; Abdullah (Pakistan Armed Forces Medical Journal, 2025)
Objectives: To compare the efficacy and complications of orogastric tubes (OGT) versus nasogastric tubes (NGT) for intraoperative gastric decompression in laparoscopic surgeries. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Anesthesiology, Combined Military Hospital, Gujranwala Pakistan, from Jan to Dec 23. Methodology: Patients undergoing laparoscopic cholecystectomy in CMH Gujranwala were included and segregated into two equal groups of 50 each on basis of method used for intra-operative gastric decompression (Orogastric and Nasogastric). The efficacy of method and associated complications of both methods were observed and compared between both groups. Results: The sampled population included 38.0% males and 62.0% females. ASA-I patients constituted 46.0% of the sample size whereas 54.0% belonged to ASA-II. The OG intubation via second ETT was significantly a better method for intraoperative gastric deflation when compared by attempts to pass the tube (p<0.001). The rate of nasal complications was significantly more in Group-B as compared to Group-A (p<0.001). A non-significant relationship was seen in terms of mean discharge time (p=0.68). Conclusion: Orogastric tube via second ETT is a safe and more effective method for reducing intraoperative gastric distension during laparoscopic surgery as compared to Nasogastric method.